Design of automated oil sludge treatment unit; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Chukhareva N. V. Natalia Vyacheslavovna (Latest Technology of Oil-and-Gas Pipelines and Petroleum Storage, 2015)
Title screen